Exploration of SDN-Based Mobility Management Mecbanism - Mingyu Zhao; Xueqiang Yan (Dianxin kexue)
Mobility management is a key technology in the mobile communication network.On the basis of analyzing the current mobility management technologies and researching SDN,an SDN-based mobility management mechanism without tunnel was presented,which was applicable to solve the existing issues such as GTP overheads,increasing signa1,non-seamless handover,and low routing efficient,and was in line with the future network trend as well.The architecture of this proposal was depicted,and the signal procedure was minutely dissected.